Achilles Tendon Regeneration can be Improved by Amniotic Epithelial Cell Allotransplantation - B. Barboni; V. Russo; V. Curini; A. Mauro; A. Martelli; A. Muttini; N. Bernabò; L. Valbonetti; M. Marchisio; O. Di Giacinto; P. Berardinelli; M. Mattioli (Cell Transplantation, 2012)
Amniotic epithelial cells (AECs) are ideal seed cells for tissue regeneration, but no research has yet been reported on their tendon regeneration potential. This study investigated the efficiency of AEC allotransplantation for tendon healing, as well as the mechanism involved. To this aim ovine AECs, characterized by specific surface and stemness markers (CD14 - , CD31 - , CD45 - , CD49f, CD29, CD166, OCT4, SOX2, NANOG, TERT), were allotransplanted into experimentally induced tissue defects in sheep Achilles tendon. In situ tissue repair revealed that AEC-treated tendons had much better structural and mechanical recoveries than control ones during the early phase of healing. Immunohistochemical and biochemical analyses indicated that extracellular matrix remodeling was more rapid and that immature collagen fibers were completely replaced by mature ones in 28 days. Moreover, spatial–temporal analysis of cellularity, proliferation index, vascular area, and leukocyte infiltration revealed that AECs induced a specific centripetal healing process that first started in the tissue closer to the healthy portion of the tendons, where AECs rapidly migrated to then progress through the core of the lesion. This peculiar healing evolution could have been induced by the growth factor stimulatory influence (TGF-β1 and VEGF) and/or by the host progenitor cells recruitment, but also as the consequence of a direct tenogenic AEC differentiation resulting in the regeneration of new tendon matrix. These findings demonstrate that AECs can support tendon regeneration, and their effects may be used to develop future strategies to treat tendon disease characterized by a poor clinical outcome in veterinary medicine.